Commonwealth of Women in Folklore and Written Literature - Himoyat Ismoilova (Genius Journals, 2022)
The article analyzes examples of folklore and the pre-Islamic social life of Uzbek classical literature, the attitude to women and the characteristics of the female image.
Keywords: Artistic creation; social life; women and society; idea